2015
DOI: 10.1177/0022034515606873
|View full text |Cite
|
Sign up to set email alerts
|

Slc26a3/Dra and Slc26a6 in Murine Ameloblasts

Abstract: Formation of apatite crystals during enamel development generates protons. To sustain mineral accretion, maturation ameloblasts need to buffer these protons. The presence of cytosolic carbonic anhydrases, the basolateral Na(+) bicarbonate cotransporter Nbce1, and the basolateral anion exchanger Ae2a,b in maturation ameloblasts suggests that these cells secrete bicarbonates into the forming enamel, but it is unknown by which mechanism. Solute carrier (Slc) family 26A encodes different anion exchangers that exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
2
27
0
4
Order By: Relevance
“…In our most recent study, the presence of a basolateral Na + ‐HCO3 cotransporter was revealed in acid‐loading experiments performed in the presence of HCO3/CO 2 in functional microfluorometric experiments using specific inhibitors (Racz et al., ). These data are in line with our RT‐PCR evidence for NBCe1 expression in HAT‐7 cells (Bori et al., ) and also with reports of tissue staining of maturation ameloblasts (Jalali et al., ). The basolateral localization of NBCe1 in these cells is similar to that observed in secretory epithelia such as the pancreatic ducts and guinea pig (Ishiguro et al., ) and also the salivary glands (Gresz et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 93%
See 1 more Smart Citation
“…In our most recent study, the presence of a basolateral Na + ‐HCO3 cotransporter was revealed in acid‐loading experiments performed in the presence of HCO3/CO 2 in functional microfluorometric experiments using specific inhibitors (Racz et al., ). These data are in line with our RT‐PCR evidence for NBCe1 expression in HAT‐7 cells (Bori et al., ) and also with reports of tissue staining of maturation ameloblasts (Jalali et al., ). The basolateral localization of NBCe1 in these cells is similar to that observed in secretory epithelia such as the pancreatic ducts and guinea pig (Ishiguro et al., ) and also the salivary glands (Gresz et al., ).…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 93%
“…However, it is clear that ameloblasts must have sufficient molecular machinery to secrete bicarbonate ions into the enamel space to buffer the eight moles of protons liberated during one mole of hydroxyapatite formation. Along with AE2 and CFTR, ameloblasts modulate changes in extracellular and intracellular pH through expression of electrogenic Na+‐HCO3 cotransporter 1 (NBCe1), Na + ‐H + exchanger 1 (NHE1), carbonic anhydrase 2 and 6 (CA2, CA6), pendrin (SLC26A4), DRA (SLC26A3), and Pat1 (SLC26A6; Damkier et al., ; Jalali et al., ; Josephsen et al., ; Lacruz, Brookes, et al., ; Lacruz et al., ). Until recently, our knowledge about electrolyte transport by ameloblasts was based almost solely on immunohistochemistry, chemical composition analysis, and expression studies in wild‐type and knockout mouse models.…”
Section: Present Knowledge On the Role Of Bicarbonate In Controlling mentioning
confidence: 99%
“…Inhibition of modulation in fluorotic enamel or enamel of Cftr ‐null and Ae2a,b ‐null mice closely follows the decrease in levels of Cl − . The most incisal modulation band in fluorotic enamel, lined by the oldest and the most‐to‐acid‐exposed ameloblasts, disappears from maturation enamel first , soon followed by more apically positioned bands at longer exposure time or at higher concentrations of F . The levels of Cl − in enamel follow this pattern closely, being lowest at the most incisal end.…”
Section: Discussionmentioning
confidence: 83%
“…Formation of hydroxyapatite releases large quantities of protons that need to be neutralized . In recent years, several groups (including ours) have identified, in maturation‐stage ameloblasts, a series of transmembrane proteins that in typical transport epithelia are involved in the production and transport of bicarbonates; these proteins include CFTR , AE2a,b , NBCE1 , Na‐hydrogen exchanger‐1, and carbonic anhydrase 2 , as well as members of solute carrier family 26 (SLC26), including Slc26a3 , Slc26a4 and Slc26a6 . A recent study confirmed that rat ameloblast‐like cells grown on transwell filter membranes functionally polarize and secrete bicarbonates across their apical plasma membranes .…”
mentioning
confidence: 99%
“…Resistance, Immunocytochemistry, RT-PCR, RT-qPCR, Microfluorometry, and Statistical Analysis The following were performed as described in the Appendix: transepithelial electrical resistance (TER) of cells on Transwell, immunocytochemical imaging for identification of cell-specific proteins Jalali et al 2015), methods identifying TJ proteins and expected electrolyte transporters by applying standard semiquantitative and quantitative polymerase chain reaction technologies to amplify the mRNA (Hegyesi et al 2015), microfluorometric measurements, and statistical analyses (Szucs et al 2006).…”
Section: Measurement Of Transepithelial Electricalmentioning
confidence: 99%